Could calisthenic exercises improve maximal exercise capacity, peripheral muscle strength and quality of life in dyslipidemia? - Furkan Özdemir; Melda Sağlam; Aydan Aslı Aksel Uylar; Oğuz A. Uyaroğlu; Nursel Çalik Başaran; Mine Durusu Tanriöver; Naciye Vardar Yağli (PLoS ONE, 2025)
Background Regular exercise improves cardiovascular health through regulating the plasma lipoprotein profile. But the effects of different exercise modalities on exercise capacity, muscle strength and quality-of-life in dyslipidemia is unclear. Objectives This study aimed to investigate the effects of calisthenic exercises on exercise capacity, muscle strength and quality-of-life in dyslipidemia. Methods Thirty-nine individuals were randomly divided into 3 groups: Aerobic + Calisthenic Exercise Group (ACG), Aerobic Exercise Group (AG) and Control Group (CG). Exercise capacity measured using cardiopulmonary exercise test, muscle strength using handheld dynamometer, quality-of-life using Short Form-36 Quality of Life Questionnaire (SF-36) at baseline and 8 weeks after. Results Peak oxygen uptake (VO2peak) (p < 0.001), metabolic equivalent (MET) (p < 0.001) and percentage of oxygen pulse increased significantly within ACG (p < 0.001). Peak heart rate (p = 0.006) and heart rate reserve improved significantly within AG (p = 0.004). Peak VO2 (p < 0.001), MET (p < 0.001), oxygen pulse (p = 0.006), knee extensor (p < 0.001) and handgrip strength decreased significantly within CG (p = 0.009). MET (p < 0.001) and %handgrip strength increased significantly in ACG compared to AG and CG (p = 0.021). Peak VO2 (p < 0.001), heart rate (p < 0.001), heart rate reserve (p < 0.001), and handgrip strength increased significantly in ACG compared to CG (p = 0.009). Peak heart rate (p < 0.001), heart rate reserve (p < 0.001) and shoulder abductor strength improved significantly in AG compared to CG (p = 0.019). Conclusions Aerobic exercises recommended for regulating blood biochemistry in dyslipidemia. But effects of calisthenic exercises in dyslipidemia are unclear. Our study showed that calisthenic exercises which combined with aerobic exercise training may improve cardiac and pulmonary response to exercise and handgrip strength in dyslipidemia. Additionally, aerobic exercise training may improve cardiac response to exercise in dyslipidemia. ClinicalTrials Number: NCT06008912.